A Study on Changing Landscape of E-Retailing in India - Rajesh, P. S.; Prasad, S. K. (Indian Journal of Computer Science, 2019)
Consumer perception towards shopping experiences has been changed with the introduction of internet media. The life style of the customers in metro cities and the time and distance is a major setback for consumers moving towards online platforms as busy scheduled life doesn’t provide much time to go and search through brick and mortar stores. This has even challenged the offline stores to create their online presence. Almost all online transactions of customers are happening through mobile and internet which involves bank information or personal data. E-commerce sites are vulnerable to cyber attacks, so security measures need to be escalated. Consumers still have a propensity towards shopping offline mainly when it comes to purchasing home appliances, considering the touch and feel factors, but with all we can say that outlook of e-retailing market is bright in India. Internet knowledge of the consumer and wider use of internet with cyber security are some of the remarkable factors which are vital for the justifiable development and growth of e-retailing in India.